I Did You a Favor By Taking Your Work: Reconsidering the Harm-Based Approach To the Fourth Fair Use Factor - Sandalow, Casey (The Columbia Journal of Law & the Arts, 2023)
American copyright law is predominantly utilitarian. Fair use—codified to promote copyright’s utilitarian goals—has emerged as one of the most nebulous doctrines in American law. This is partially by design. Passing the Copyright Act of 1976 (the “Act”), Congress sought to endorse “the purpose and general scope of the judicial doctrine of fair use,” but made clear that “there is no disposition to freeze the doctrine in the statute, especially during a period of rapid technological change.” This judicial deference—combined with the case-by-case nature of fair use determinations—has led to evolving and inconsistent applications of section 107. Interpretation of section 107(4), which instructs courts to consider “the effect of the use upon the potential market for or value of the copyrighted work,” is illustrative. Though a plain reading of section 107(4) leaves room for consideration of all market effects, most courts and commentators agree that the inquiry into this factor concerns only deleterious effects on the copyright owner’s actual or potential markets. Some have expressed hostility toward consideration of positive market effects on the ground that an infringing use that might improve sales of a copyrighted work is also likely to invade the market for derivative works. In limited circumstances, courts and commentators have recognized the relevance of an unauthorized use providing financial gain for a copyright holder. In Authors Guild, Inc. v. Google Inc., Judge Chin indicated that Google Books increased exposure and sales for the copyright holders, concluding that “the fourth factor weighs strongly in favor of a finding of fair use.” While the Second Circuit declined to adopt Judge Chin’s explicit reasoning, Authors Guild remains a powerful endorsement of the plain reading of section 107(4). In Google LLC v. Oracle Am., Inc., the Supreme Court indicated that analysis of the fourth factor should weigh public benefits against private harms, endorsing a more holistic balancing of interests. In the wake of a reinvigorated fourth factor, it is worth reassessing whether economic benefits from infringement have any place in the market impact inquiry. This Note addresses the current status of market benefits: monetary gains conferred upon a copyright holder by a third party’s unauthorized use of a copyrighted work. While courts are still unwilling to treat market benefits as dispositive, they are moving away from the view that the fourth factor concerns only market harm. Expanded analysis of a fourth factor now balances private economic effects, public benefits, and in some cases, non-monetary concerns related to the value of a work. Market benefit proponents assert that their inclusion is more in line with the text and history 1976 Act, as well as the overall goals of copyright. Further, weighing market benefits against market harms helps to address problems related to circularity. This Note considers the viability of market benefits as both a dispositive and a relevant component of fourth factor interpretation. Part I provides a basic overview of the traditional approach to the fourth factor before defining and distinguishing between different types of market benefits. Part II analyzes recent caselaw acknowledging market benefits and proposes a framework for proving market benefits as part of a reinvigorated fourth factor. Part III addresses the viability of market benefit arguments across different sectors of copyrighted works and the possible implications of increased acceptance. It concludes that, despite enhanced recognition, market benefits still lack widespread applicability and are unlikely to change the outcome of any present fair use determination.